2009
DOI: 10.1590/s1516-89132009000600002
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-anatomical and micromorphometrical evaluations in soybean genotypes during water stress

Abstract: In a greenhouse experiment, morpho-anatomical and micromorphometrical analyses of two soybean cultivars

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Thus, in many species such as, Ctenanthe setosa and Triticum aestivum, the entire lamina and mesophyll thickness were reduced under drought stress [2][3][4][5][6][7][8][9][10][11][12][13][14], while it was unaffected by water stress in salvia spendens and Glycine max [13][14][15][16]. Bussotti et al [17] found that limited soil moisture caused a major thickening of the mesophyll, especially in the leaf cuticle and spongy parenchyma of the beech plant, Fagus sylvatica. Multiple characteristics of vascular structure have been investigated, such as modifications of the vascular bundle number and area and alteration of xylem/ phloem ratio, which are thought to be involved in the resistance of the plant to environmental stresses [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in many species such as, Ctenanthe setosa and Triticum aestivum, the entire lamina and mesophyll thickness were reduced under drought stress [2][3][4][5][6][7][8][9][10][11][12][13][14], while it was unaffected by water stress in salvia spendens and Glycine max [13][14][15][16]. Bussotti et al [17] found that limited soil moisture caused a major thickening of the mesophyll, especially in the leaf cuticle and spongy parenchyma of the beech plant, Fagus sylvatica. Multiple characteristics of vascular structure have been investigated, such as modifications of the vascular bundle number and area and alteration of xylem/ phloem ratio, which are thought to be involved in the resistance of the plant to environmental stresses [18].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing LA is a drought avoidance strategy for the plants by reducing transpiration and avoiding low water potential which allows more water uptake (Villagra and Cavagnaro, 2006). Relative growth rate (RGR) is an efficient physiological index for comparing effects of agronomic characters (Stolf et al, 2009); RGR was high at the beginning of the experiment for the three vetch species and decreased significantly from 71-105 DWT. Indeed, in early stages, plants are in vegetative growth phase and from 91 DWT, flowering starts in V. narbonensis.…”
Section: Discussionmentioning
confidence: 99%
“…Skirycz & Inzé (2010) emphasize that under abiotic stresses plants actively re-program their growth, recover it and adapt themselves, once stress conditions become stable. These mechanisms of adaptation and stress tolerance are called by Kroon et al (2005) "plant plasticity", which may be more related to specific parts of plants, as seen in soybean (Stolf et al 2009) and in Pereskia species (Leuenberger 1992).…”
Section: Key-wordsmentioning
confidence: 99%